The Nexus of Stem Cell-Derived Beta-Cells and Genome Engineering (The Review of Diabetic Studies, 2017)
Diabetes, type 1 and type 2 (T1D and T2D), are diseases of epidemic proportions, which are complicated and defined by genetics, epigenetics, environment, and lifestyle choices. Current therapies consist of whole pancreas or islet transplantation. However, these approaches require life-time immunosuppression, and are compounded by the paucity of available donors. Pluripotent stem cells have advanced research in the fields of stem cell biology, drug development, disease modeling, and regenerative medicine, and importantly allows for the interrogation of therapeutic interventions. Recent developments in beta-cell differentiation and genomic modifications are now propelling investigations into the mechanisms behind beta-cell failure and autoimmunity, and offer new strategies for reducing the propensity for immunogenicity. This review discusses the derivation of endocrine lineage cells from human pluripotent stem cells for the treatment of diabetes, and how the editing or manipulation of their genomes can transcend many of the remaining challenges of stem cell technologies, leading to superior transplantation and diabetes drug discovery platforms.